Confronting built heritage: Shifting perspectives on colonial architecture in Indonesia - Pauline K. M. van Roosmalen (ABE Journal)
From the 1990s to the present, newspapers in Indonesia, notably Sunday editions, have regularly featured articles appreciative of Indonesia’s colonial built heritage. Often the work of relatively young reporters, the articles either praised the aesthetics and historical relevance of the buildings and townscapes or highlighted the threats facing them. To most non-Indonesians, notably Europeans and Americans, the relaxed and positive attitude towards these tactile and often prominent reminders of Indonesia’s colonial past is quite a novelty. The sight of Indonesians in mock-colonial outfits exploring this heritage on vintage Dutch bikes provokes sheer astonishment.By describing the changing appreciation of Indonesia’s colonial built heritage and the agents that drove this development, this article analyses how Indonesia and the Netherlands gradually appropriated the built heritage of their colonial past.